KELAYAKAN KOMIK HASIL INVENTARISASI JAMUR DI GUNUNG TUNGGAL PADA MATERI KEANEKARAGAMAN HAYATI - Rafika yarso; Eka Ariyati; Laili Fitri Yeni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the feasibility of the comic media of makrofungi diversity in the Mount Forest Preserve Tunggal of Semayang village’s makrofungi inventory result as a learning medium for SMA class X’s biodiversity study and to determine the types of makrofungi which are available in Mount Forest Preserve Tunggal of Semayang village. The research was quantitative with descriptive method. Samples were taken using purposive sampling with cruising method. The results of the research found  as many as 41 types of fungi from 21 families in 2 division (Basidiomycota and Ascomycota). Basidiomycota division includes Agaricaceae, Amanitaceae, Auricullariaceae, Bolbitiaceae, Clavariaceae, Fomitopsidaceae, Ganodermataceae, Hymenochaetaceae, Incertaceae sedis, Inocybaceae,  Lyophyllaceae, Marasmiaceae, Meripilaceae, Meruliaceae, Mycenaceae, Plutuaceae, Polyporaceae, Russulaceae, Serpulaceae and Streaceae families, while the Ascomycota division include Sarcoscyphaceae family. The result of comic assessment carried out by 5 validators is valid with the average score of CVI 1, so that it can be properly used as a medium of learning in the topic of biodiversity. Keywords: Inventory, Makrofungi, Comic